Filmes de polissacarídeos naturais para a veiculação cutânea de nanocápsulas de silibinina no tratamento da dermatite atópica - Gehrcke, Mailine (2022)
Current treatments for atopic dermatitis have restrictions adverse effects, and there is a need to develop therape due to the limited efficacy and pronounced utic alternatives. Thus, this study aimed to associate the potential of nanocapsules with the advantages provided by polymeric films, in order to develop a new topical formulation containing silibinin (SB), an antioxidant and anti flavonoid, finflammatory or atopic dermatitis treatment. The nanocapsule suspensions were prepared by the interfacial deposition method of the preformed polymer, using ethylcellulose and medium chain triglycerides, and showed nanometric size, polydispersity index below 0.2, negati ve zeta potential, acidic pH, SB content and encapsulation efficiency of about 100 %. Subsequently, these suspensions were incorporated into gellan gum films by the solvent deposition/evaporation method, using glycerol as plasticizer. For comparative purpo ses, vehicle films and films containing the nonnanoencapsulated flavonoid were also prepared. The developed films were thin, transparent, flexible and with swelling capacity greater than 100 %, remaining intact after 24 h in contact with pH 7.4 buffer. Th e film's irritation potential was evaluated by the chorioallantoic membrane test, which showed the formulations biocompatibility. Also, compared to films containing free SB, nanobased films showed greater occlusive property and better stability during st orage at room temperature. The in vitro release assay showed that the films containing the nanoencapsulated flavonoid had a controlled release profile, which is in agreement with the cutaneous permeation profile obtained. Despite the controlled release, it was possible to quantify therapeutic amounts of SB in the target layers for the skin diseases treatment (epidermis and dermis). In a second stage of the work, the feasibility of producing bilayer films of gellan gum/pullulan using the same preparation met hod was demonstrated. For this, a pullulan aqueous dispersion was cast onto the partially dried gellan gum layer containing nanocapsules. The bilayer films demonstrated a welltwolayer microstructure, which was evaluated by scanning electron micro defined scopy. Furthermore, the addition of the pullulan layer was able to give bioadhesive and less stiff characteristics to the films, as well as increasing their occlusive potential by about 2 times, without altering the profiles of release and cutaneous permea tion of SB. The antioxidant performance of the bilayer films containing silibinin nanocapsules was evaluated using the ABTS radical, which showed the high scavenger capacity of this flavonoid. It was also demonstrated that bilayer films are hemo/biocompati ble through a direct contact hemolysis assay. Finally, the biological performance of bilayer films was evaluated in an animal model of dinitrochlorobenzene induced atopic dermatitis. The association of SB nanocapsules into gellan/pullulan gum bilayer films attenuated dermatitislike lesions in mice, as well as modulating oxidative and inflammatory parameters. In conclusion, the incorporation of nanocapsules into gellan gum films provides greater stability and is able to control the skin release/permeation o f SB. Also, in the context of cutaneous application, the characteristics of these films can be improved by adding a pullulan layer, which is a novel and promising strategy for atopic dermatitis treatment.